A new species of pencil smelt Nansenia boreacrassicauda (Microstomatidae, Argentiniformes) from the North Atlantic Ocean - Poulsen, Jan Yde (Zootaxa, 2015)
A new microstomatid oceanic species, Nansenia boreacrassicauda spec. nov., is described from the temperate and subarctic Atlantic Ocean. The new species is part of the “stubby caudal peduncle” group and includes the northernmost record of any Nansenia species close to the Arctic Circle. The new species is putatively most similar to the Mediterranean Nansenia iberica, distinguished by a smaller caudal peduncle length/depth ratio, a smaller predorsal distance, more gill rakers, a different lateral line scale type and distribution. Extended Nansenia species distributions and specimens that show extralimital characters in relation to previous works are presented, addressing the current problematic taxonomic issues prevalent in pencil smelts and closely related genera. The new species is described due to increased collecting and taxonomic efforts off Greenland and is not necessarily related to ocean temperature changes.